The Composition of Gut Microbiota in Patients Bearing Hashimoto’s Thyroiditis with Euthyroidism and Hypothyroidism - Simo Liu; Yaxin An; Bin Cao; Rongxin Sun; Jing Ke; Dong Zhao (International Journal of Endocrinology)
Aims. Hashimoto’s thyroiditis (HT), a type of autoimmune disease, occurs due to genetic predisposition and environmental factors. It is well known that thyroid function may affect the gut microbiota. However, the composition of gut microbiota in HT patients with different thyroid function status has been less highlighted. Therefore, we focused on the alterations in the composition of gut microbiota in HT patients with euthyroidism and hypothyroidism. Methods. We performed a cross-sectional study, including 45 HT patients with euthyroidism, 18 HT patients with hypothyroidism, and 34 healthy controls. Fecal samples were collected, and microbiota was examined by using 16S RNA ribosomal RNA gene sequencing. Then, we analyzed the possible pathways in relation to the enriched bacteria by linear discriminant analysis (LDA) effect size (LEfSe). Results. Compared with the controls, bacterial richness and diversity were significantly lower in patients with HT, especially in hypothyroidism. Moreover, Lachnospiraceae_incertae_sedis, Lactonifactor, Alistipes, and Subdoligranulum were more enriched in HT patients with euthyroidism, while Phascolarctobacterium was more abundant in those with hypothyroidism. Further analysis suggested that Phascolarctobacterium was negatively related to several pathways, including environmental information processing and metabolism. Conclusion. In summary, our study demonstrated the altered composition of gut microbiota in HT patients with different thyroid function status. Moreover, Phascolarctobacterium may be involved in the development of HT.